Proposta de metodologia simplificada para avaliação da qualidade posicional de imagens orbitais de alta resolução: um estudo de caso em uma região da Amazônia Oriental - ESPINDOLA, Wesley Jordan da Silva (2024)
In view of the importance of cartographic products and their degree of accuracy for studies in different areas, this research deals with the geometric correction of a CBERS-4A image in order to assess its planimetric accuracy, using data from the land collection as a reference in the georeferencing stage. In addition, data from rural property parcels was filtered, the concentration of property vertex points was identified, and the accuracy values obtained were classified according to PEC and PEC-PCD standards. The methodological stage was divided into four parts, starting with data collection, processing, application and finally the calculation of Root Mean Square Error (RMSE) values for 55 control points and 15 check points, selected from the point cloud generated with SIGEF data. As a result, it was possible to obtain variations in positional accuracy values, based on the number of control points used, which varied from the 1:1,000 Class A scale in the PEC standards and 1:1.000 Class B scale for PEC-PCD georeferencing with up to 35 points to the 1:2.000 Class B scale of PEC and 1:2.000 Class C scale of PEC-PCD for the product of 55 control points used. Therefore, it was possible to conclude that the use of SIGEF data can be a viable alternative for collecting the information needed to georeferenced images, without the need for field collection, contributing to the control of re- mote locations that are difficult to access and reducing costs to produce cartographic docu- ments.